2017
DOI: 10.1111/cxo.12431
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of accommodation in an 11‐ to 17‐year‐old Iranian population

Abstract: This study showed that the AA in Iranian teenagers is lower than that calculated with Hofstetter's formula. It is important to take account of this point when making diagnostic and therapeutic decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
1
25
1
Order By: Relevance
“…As AA measurement protocols were similar in terms of methods (the push‐up method), tools and accommodative target, the different findings in these two studies cannot be attributed to measurement differences. Although factors such as differences in race, nutrition, climate and education can be the possible causes of such inter‐study differences, we believe the results of the two previous studies should be judged and compared with caution in light of the small samples and the lack of random sampling. The findings of the present study, which rely on a large sample and population‐based sampling, showed the limitation of Hofstetter's equation for accurate AA estimates in children.…”
Section: Discussionmentioning
confidence: 99%
“…As AA measurement protocols were similar in terms of methods (the push‐up method), tools and accommodative target, the different findings in these two studies cannot be attributed to measurement differences. Although factors such as differences in race, nutrition, climate and education can be the possible causes of such inter‐study differences, we believe the results of the two previous studies should be judged and compared with caution in light of the small samples and the lack of random sampling. The findings of the present study, which rely on a large sample and population‐based sampling, showed the limitation of Hofstetter's equation for accurate AA estimates in children.…”
Section: Discussionmentioning
confidence: 99%
“…One way ANOVA showed showed significance (p=0.000). Our results show that ageexpected method in majority of the cases could provide the clear and comfortable vision at near [10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…A distance exophoria more than 3 prism diopters or any distance esophoria was considered abnormal distance heterophoria. An accommodative amplitude below the expected minimum amplitude for age according to the Hofstetter's formula (15–0.25 age) 22 was regarded as an abnormal accommodative amplitude. A SCCO score ≤ +2 for the saccadic and pursuit movements was considered abnormal.…”
Section: Methodsmentioning
confidence: 99%